“I feel as lonely as a wreck at sea”: Reviewing Fernando Pessoa’s Youth Literary Identity, Charles Robert Anon - Colom Jiménez, María (Complutense Journal of English Studies, 2024)
When initiating the journey to explore Fernando Pessoa’s (1888-1935) literary world, one rapidly becomes conscious of the vast literary output developed by the author. With means of understanding his whole literary universe, it must be acknowledged that Pessoa was bilingual, and that English, and Portuguese language cohabited in his literary universe. One is struck by astonishment when discovering that there are in fact so many English-writing literary characters, so many texts, anthologies, fragments, and literary projects in English. This study revises Pessoa’s pre-heteronymic process and the creation of English literary characters who are introduced into a dialogical chain, which later becomes a more serious literary depersonalisation process in his adulthood. By revising Pessoa’s youth companion Charles Robert Anon, this study intends to outline the Portuguese authors literary process and the starting point and evolution of what later became his most exceptional concept: the heteronyms. Through his character and the texts he signed, Anon represents young Pessoa’s “intellectual anxieties and existential concerns of a young intellectual entering adulthood” (Zenith in Pessoa 2001: 7). This study sustains that the edition, publication, translation, and critical analysis of the totality of Anon’s literary production is an important element to shed light in the understanding of Pessoa’s drama-in-people and adult writings.